START-UP CULTURE WITH A SOCIAL CONSCIENCE: MANAGING CREATIVE TECHNOLOGIES FOR SUSTAINABLE IMPACT - Pipit Sundari; Miku Fujita; Daiki Nishida (Journal of Social Entrepreneurship and Creative Technology, 2026)
Start-ups increasingly operate within a landscape where technological innovation intersects with social responsibility, yet empirical understanding of how these ventures manage creative technologies for sustainable impact remains limited. This study addresses the critical gap in knowledge regarding the operationalization of ethical objectives within technology-driven entrepreneurial contexts. The research aims to investigate the strategies, organizational practices, and mechanisms through which socially-conscious start-ups leverage creative technologies to achieve measurable social and environmental outcomes. A qualitative multiple-case study design was employed, involving ten start-ups in the creative technology sector. Data collection comprised semi-structured interviews with founders and key team members, systematic observations of operational processes, and document analysis including mission statements and project reports. Thematic coding and triangulation were applied to identify patterns, relationships, and emergent strategies in aligning technological adoption with social objectives. Findings reveal that intentional integration of technology with organizational culture and resource allocation significantly enhances social impact, while collaborative team structures and iterative feedback mechanisms reinforce ethical operational practices. Variations across cases highlight the influence of managerial decision-making and sectoral context on effective implementation of social initiatives. Start-ups that align creative technologies with social conscience achieve both operational efficiency and sustainable societal benefit. The study concludes that responsible innovation is contingent upon deliberate strategic planning, technological competence, and ethical leadership, providing a framework for guiding future socially-conscious entrepreneurial endeavors.